Peran Dinas Sosial PPPA Dalam Menangani Gelandangan Pengemis (GEPENG) di Kota Probolinggo - N, Veronica Sri Astuti; Y, Eko Yudianto; Apriliansah, Feri (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The problem of homeless and beggars is currently still a concern of the local government. Not only in big cities, even in small towns there are still many homeless beggars (GEPENG) such as in Probolinggo City. Many motives are carried out by someone to make the culture of begging and the homeless as a profession. In dealing with this problem, the Probolinggo city government through the Social Service for Women's Empowerment and Child Protection (PPPA) continues to make efforts to minimize the presence of homeless beggars on the streets. This research aims to find out and obtain an overview of the role and strategy of the PPPA service in dealing with the GEPENG problem in Probolinggo City. This research uses a qualitative descriptive method. Data collection techniques are carried out through observation, interviews and documentation. The selection of informants is selected according to the criteria that are considered to be able to provide answers that are in accordance with the problem. This research uses role theory according to J. Dwi Narwoko and Bagong Suyanto (2010:160) as an analysis material. The results of this research show that the PPPA Social Service in dealing with Homeless Beggars (GEPENG) in Probolinggo City is in accordance with Probolinggo Mayor regulation number 38 of 2019 with the availability of temporary shelter houses (Shelters) including their managers as a place for fostering Homeless Beggars (GEPENG), coordination with Satpol PP. The obstacle in dealing with the GEPENG problem is the limited temporary shelter (Shelter) for Homeless Beggars (GEPENG) so that the capacity is inadequate.